Case Concerning the Frontier Dispute (Burkina Faso/Republic of Mali) Volume II: Memorial of Mali and Annexes to the Memorial - International Court of Justice (United Nations, 2024)
These five volumes contain pleadings from the case concerning the Frontier Dispute (Burkina Faso/Republic of Mali) in the language in which they were submitted, including the document instituting proceedings, the written pleadings and their annexes, the verbatim records of the oral proceedings, and any documents submitted to the Court after the closure of the written proceedings.